Deforestation and Agricultural Expansion Processes in Gunung Palung National Park, West Kalimantan, Indonesia - Franky Zamzani; Nariaki Onda; Kunihiko Yoshino; Misa Masuda (Institut Pertanian Bogor (IPB University), 2009)
Gunung Palung National Park (GPNP) represents the biodiversity of tropical forests remain in Kalimantan Island. However, the natural ecosystem has been threatened by human impact. This study aimed (1) to identify the deforestation process inside the national park by imagery analysis of Landsat TM (1992), Landsat ETM+ (1999), and SPOT5 (2004), and (2) to find the driving forces behind agricultural expansions. The results showed that forest cover of GPNP decreased by 18.7% (equal with 18,675) at an average rate of 1.6% per year from 1992 to 2004. Land use changes by illegal logging were accelerated after decentralization (1,064 ha in 1992-1999 to 3,781 ha in 1999-2004). In the other side, increase of mix garden/bush area inside GPNP was relatively constant (4,555 ha in 1992-1999 to 9,040 ha in 1999-2004). Results also showed tendency on increasing areas for dry-rice cultivation and rubber plantation (averagely 2.0 ha per household). The study also revealed that secondary forest has constantly decreased in GPNP annually. Family size and income were considered as important factors that were driving forces of deforestation. To this, zoning system of the national park by clear participatory demarcation and application of effective buffer-zone support programs were recommended.Keywords: deforestation, agricultural expansion, national park, imagery analysis, zoning system